Dental caries prevalence in children and youths with vertically-transmitted HIV/AIDS from the pediatric HIV clinic (Cali, Colombia) and its relationship with biological factors, 2013 - María Cristina Arango-de la Cruz; Carlos Alberto Velasco-Benítez; Pío López-López (Universidad de Antioquia, 2018)
Introduction: among the oral pathologies afflicting children with HIV/AIDS is dental caries, a preventable disease if detected and controlled in its early stages to avoid further complications. The aim of this study was to determine the prevalence of caries in children and youths with vertically-transmitted HIV/AIDS from the Pediatric HIV Clinic in Cali, Colombia, in 2013, and to explore relationships with biological factors. Methods: descriptive prevalence study in 101 clinical records of children and youths aged 1 to 17 years with vertically-transmitted HIV/AIDS from the Pediatric HIV Clinic in Cali. The ICDAS and DMF/def classification systems were used. Multivariate analysis and confounding variable adjustment were included to explore relationships with demographic, paraclinical, nutritional, and dental factors. The institutional ethics committees endorsed the study. Results: the prevalence of caries experience in children with HIV was 34.65% DMF/deft (5-6) 3.29 ± 3.06. This prevalence increases 83.17% with the ICDAS 2-6 system. The point prevalence of active caries was 74.26% DMFT 5.68 ± 5.48. No statistically significant association was found with any socioeconomic or immunologic variables. Patients with moderate to severe immunosuppression had OR 1.13 CI95% (0.33-3.81) p = 0.84. A probable association was found with plaque index OR 4.58 CI95% (1.44-14.55) p = 0.006 and caries experience OR 4.21 CI95% (1,09-16.13) Conclusion: HIV patients from the Pediatric Clinic show high caries prevalence when pre-cavitated lesions are assessed. No probable association was found between caries and immunological or clinical status, and therefore this aspect is not an additional risk factor.